Application of Internet of Things in Multiple Tanks water level controlling - Ashfaque Ahmed, Siddiqui Ahmed Mohsin, Faheem Ansari, Shah Awais, Fahad Bilal (International Journal of Advanced Science and Technology, 2020)
This paper presents the improvement in the past work by changing the programming of the 8051 microcontroller and web page programming. The adjustment in the programming of 89S52 microcontroller is done and because of which the Administrator can control the individual tank water level by turning on/off relays which thusly controls the solenoid valve open/close. In manual method of administrator login four new tabs will show up on site page marked as Relay1 On/OFF, Relay2 On/Off, Relay3 On/Off and Relay 4 On/Off. In manual mode set motor on/off tab shows up on site page just when each of the 4 tanks get filled totally with water. The administrator can control the individual tank water level without turning motor on/off each time. The motor will be off physically when every one of the 4 tanks are filled 100% at that point water pump motor can be turned off by utilizing motor off the tab.